2016
DOI: 10.1101/038778
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimistic reinforcement learning: computational and neural bases

Abstract: While forming and updating beliefs about future life outcomes, people tend to consider good news and to disregard bad news. This tendency is supposed to support the optimism bias. Whether learning bias is specific to "high-level" abstract belief update or a particular expression of a more general "low-level" reinforcement learning process is unknown. Here we report evidence in favor of the second hypothesis. In a simple instrumental learning task, participants incorporated worse-than-expected outcomes at a low… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(71 citation statements)
references
References 68 publications
15
56
0
Order By: Relevance
“…The current set of results strongly support a valence dependent asymmetry in how participants update their beliefs, consistent with a large body of fast growing research (Eil and Rao, 2011, Garrett and Sharot, 2014, Garrett et al, 2014, Korn et al, 2012, Krieger et al, 2016, Kuzmanovic et al, 2015, Kuzmanovic et al, 2016, Lefebvre et al, 2016, Ma et al, 2016, Möbius et al, 2012, Sharot, 2011, Sharot and Garrett, 2016, Sharot et al, 2011, Sharot, Guitart-Masip et al, 2012). By pitting this asymmetry against three robustness tests suggested by critics of optimism (Shah et al, 2016) we find that it survives each of these tests, suggesting it is a pervasive phenomenon.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The current set of results strongly support a valence dependent asymmetry in how participants update their beliefs, consistent with a large body of fast growing research (Eil and Rao, 2011, Garrett and Sharot, 2014, Garrett et al, 2014, Korn et al, 2012, Krieger et al, 2016, Kuzmanovic et al, 2015, Kuzmanovic et al, 2016, Lefebvre et al, 2016, Ma et al, 2016, Möbius et al, 2012, Sharot, 2011, Sharot and Garrett, 2016, Sharot et al, 2011, Sharot, Guitart-Masip et al, 2012). By pitting this asymmetry against three robustness tests suggested by critics of optimism (Shah et al, 2016) we find that it survives each of these tests, suggesting it is a pervasive phenomenon.…”
Section: Discussionsupporting
confidence: 89%
“…Numerous studies spanning behavioural economics (Eil and Rao, 2011, Krieger et al, 2016, Krieger et al, 2014, Möbius et al, 2012), psychology (Garrett and Sharot, 2014, Kuzmanovic et al, 2015, Moutsiana et al, 2013) and neuroscience (Garrett et al, 2014, Korn et al, 2012, Kuzmanovic et al, 2016, Lefebvre et al, 2016, Ma et al, 2016, Moutsiana et al, 2015, Sharot, Guitart-Masip et al, 2012, Sharot et al, 2011, Sharot, Kanai et al, 2012) have shown that people alter their beliefs to a greater extent in response to good news than bad news. This asymmetry can lead to a positive bias in beliefs regarding oneself, referred to as the superiority illusion (Hoorens, 1993, Kruger and Dunning, 1999, Svenson, 1981), and in beliefs regarding one’s future, referred to as unrealistic optimism (Calderon, 1993, Radcliffe and Klein, 2002, Shepperd et al, 2005, Weinstein, 1980, for review see Sharot & Garrett, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to reduced reversal learning, and in accordance with a previous study (10), another behavioural feature that distinguished higher and lower bias participants was the preferred response rate in the Symmetric condition. In the Symmetric condition, both cues had the same reward probabilities (50%), such that there was no intrinsic "correct" response, allowing us to calculate a "preferred" response rate for each participant (defined as the choice rate of the option most frequently selected by a given participant, i.e.…”
Section: Discussionsupporting
confidence: 88%
“…We submitted the preferred choice rate to an ANOVA with experiment (1 or 2) and bias level (high and low) as between-subjects factors. The ANOVA showed a significant main effect of bias level higher biases were associated with an increased tendency to develop a preferred choice, even in the absence of a "correct" option, which naturally emerges from overweighting positive outcomes (10).…”
Section: Behavioural Signatures Of Learning Biasesmentioning
confidence: 92%
See 1 more Smart Citation